Muscle-Targeted Gene Therapy of Charcot Marie-Tooth Disease is Dependent on Muscle Activity - Klossner, Stephan; Giraud, Marie-Noëlle; Oliver, Sara Sancho; Vaughan, David; Flück, Martin (IntechOpen, 2011)
None